A better understanding of the cryogenic environment and the effect of nozzle location on the machinability of low carbon steel. (February 2022) - Salame, Charlie; Bejjani, Roland
Abstract: Cryogenic machining of metals has emerged as a sustainable machining method in manufacturing industries. This research paper presents a better understanding of the cryogenic effect during cryogenic machining of low carbon steel by varying the nozzle location in terms of separation distance from the tool-chip interface and inclination angle from the vertical. Finite Element and Computational Fluid Dynamics simulations are used to compare the cooling effect for each nozzle location, while the experiments compare the cutting forces to determine the optimal nozzle location for industrial use. The simulations recreate the complex cryogenic environment from the nozzle to the tool-chip geometry to give a better understanding of the cryogenic effect. The dominant nozzle parameter affecting the results is determined to be the separation distance, and the optimal nozzle position to ensure the minimum cutting forces is the smallest separation distance and smallest inclination angle from the vertical. The convection coefficient is shown to be variable across the tool-chip interface and related to the static pressure and evaporation rates of the cryogenic fluid. Finally, tool wear and workpiece surface roughness are shown to benefit from cryogenic application, indicating a practical solution to optimize cryogenic systems for industrial use.